Bortezomib washout duration prior to stem cell mobilization in patients with newly diagnosed multiple myeloma. (23rd March 2020) - Luttwak, Efrat; Amit, Odelia; Avivi, Irit; Trestman, Svetlana; Eshel, Rinat; Cohen, Yael C.; Ram, Ron
Abstract: Objectives: We aimed to determine the impact of washout period in patients with multiple myeloma between bortezomib‐based induction regimens and the collection of stem cells. Methods: This was a single‐center historical prospective study, including all sequential newly diagnosed patients with myeloma between 2012 and 2017 that were given a first‐line bortezomib‐based induction therapy (≤6 cycles) followed by stem cell collection (n = 75). Results: We found a statistically significant correlation between the days from last dose of bortezomib and both CD34 + cells/kg yield on the first collection day and the overall collected CD34 + cells/kg ( r = .466, P < .001, and r = .341, P = .03, respectively). The optimal receiver operating curve's cutoff point was 8.5 days (79% sensitivity and 71% specificity, P = .001). On multivariate analysis, timing of last dose of bortezomib remained statistically significant ( P = .01). Based on this, we developed a model to predict the total collected CD34 + cells/kg = 11.76 + 0.13 (timing in days of last dose of bortezomib) −0.1 (age) −1.39 (if female) −0.01 (≥PR) −1.35 (if prior radiation). Conclusions: Timing of last dose of bortezomib may predict a successful collection. A washout period of 9 days is associated with a better collection yield. A prospective validation of this novel finding is required.